EFFECT OF REPLACING COMMERCIAL RATIONS WITH PROBIOTIC-FERMENTED BAKERY WASTE IN DIETS ON BROILER PERFORMANCE - O. G. I., Putri; Nuriyasa, I M.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the effect of feeding probiotic fermented bread waste rations on broiler performance. The research was conducted at the Farm of Faculty of Animal Husbandry, Udayana University, Jalan Raya Sesetan, Denpasar. The study used a completely randomized design consisting of five treatments and four replications. The five treatments consisted of R0 (commercial ration without probiotic bread waste), R1 (commercial ration 90% + 10% probiotic fermented bread waste 1% Probio-BaliTani), R2 (commercial ration 85% + Submitted Date: June 12, 2023 Accepted Date: September 3, 2023 Submitted Date: November 12, 2020 Accepted Date: January 3, 2021 Editor-Reviewer Article: Eny Puspani & A.A. Pt. Putra Wibawa Editor-Reviewer Article : Ni Putu Mariani & Dsk. Pt. Mas Ari Candrawati Putri, O. G. I.., Peternakan Tropika Vol. 12 No. 2 Th. 2024: 17 – 30 Page 18 15% probiotic fermented bread waste 1% Probio-BaliTani), R3 (commercial ration 80% + 20% probiotic fermented bread waste 1% Probio-BaliTani) and R4 (commercial ration 75% + 25% probiotic fermented bread waste 1% Probio-BaliTani). The observed variables were ration consumption, final body weight, body weight gain and FCR. The results showed that broiler consumption in the R0 treatment was not significantly higher (P>0.05) among treatments. In the final body weight variable and additional body weight, the R0 treatment was significantly higher (P < 0.05) among treatments. FCR in treatment R0 was not significantly lower (P>0.05) than R1 and R2, but significantly lower (P<0.05) than R3 and R4. The conclusion of this study is that the replacement of commercial rations with probiotic fermented bakery waste up to 25% in broilers reduces broiler performance, but the provision of 10% and 15% does not affect FCR.